The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/onc.2009.128
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FLJ10540 is correlated with aggressiveness of oral cavity squamous cell carcinoma by stimulating cell migration and invasion through increased FOXM1 and MMP-2 activity

Abstract: Matrix metalloproteinase (MMP)-2 plays critical roles in tumor development and in the metastasis of multiple cancers, including human oral cavity squamous cell carcinoma (OCSCC). One of the upstream regulators of MMP-2 is FOXM1, which is overexpressed in a microarray dataset of OCSCC. It is interesting that FLJ10540 exhibits similar gene expression profiles with MMP-2 and FOXM1, raising the possibility that these molecules might participate in MMP-2-elicited cancer progression and metastasis of OCSCC. To exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 41 publications
6
87
0
Order By: Relevance
“…Several pathways have been proposed and recent studies have pointed to a considerable role for FOXM1 in invasion and metastasis [8,26]. It FOXM1 has been shown to regulate transcription of c-Jun N-terminal kinase ( JNK1) gene to promote the G1/S transition and tumor cell invasiveness, partly by upregulating the expression of the matrix metalloproeinases (MMPs) 2 and MMP9, both of which are crucial in the processes of tumor cell invasion and metastasis for MMPs can directly degrade the basement membrane collagen at tumorinvasive front and enable cancer cells to overcome the extracellular matrix (ECM) barrier leading to metastasis [27,28]. In lung cancer cells, combining radiation therapy with MMP2 down regulation is more e ective than radiation alone, and such a strategy involves abrogation of FOXM1 activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways have been proposed and recent studies have pointed to a considerable role for FOXM1 in invasion and metastasis [8,26]. It FOXM1 has been shown to regulate transcription of c-Jun N-terminal kinase ( JNK1) gene to promote the G1/S transition and tumor cell invasiveness, partly by upregulating the expression of the matrix metalloproeinases (MMPs) 2 and MMP9, both of which are crucial in the processes of tumor cell invasion and metastasis for MMPs can directly degrade the basement membrane collagen at tumorinvasive front and enable cancer cells to overcome the extracellular matrix (ECM) barrier leading to metastasis [27,28]. In lung cancer cells, combining radiation therapy with MMP2 down regulation is more e ective than radiation alone, and such a strategy involves abrogation of FOXM1 activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated FoxM1 in tumorigenesis, as it is overexpressed in various human cancers including lung cancer (24)(25)(26)(27)(28). Wang and colleagues showed that proliferation of lung tumor cells was diminished in Mx-Cre FoxM1 À/À mouse mutants and that these mice had a significant reduction in the number and size of lung adenomas (28).…”
Section: Introductionmentioning
confidence: 99%
“…investigation of OcScc progression from a genetic perspective has identified distinct patterns and timings of genetic alterations (3). the most important prognostic factors in OcScc are those that form part of the grading system, including tumor stage and lymph node status (4)(5)(6). The identification of new prognostic factors linked to OcScc initiation and progression may aid in the development of new diagnostic tools and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%